Family-owned businesses: towards a model of succession planning in Malaysia - Abdullah, Moha Asri; Abdul Hamid, Zarinah; Hashim, Junaidah (World Business Institute, 2011)
Succession planning for businesses is highly essential. The essence of succession planning is crucial especially among small and medium businesses as they cannot afford to withstand various major setbacks for continuity and sustainability in developing and developed countries alike. Malaysia is not exceptional to this. This present paper focuses on succession planning in family-owned retailing and manufacturing businesses of East Cost Economic Region (ECER) in Malaysia. This paper attempts to delineate three succession issues in family business i.e., succession dilemma, successor attributes and succession plan. This paper argues that to a certain extent, SME owners face some dilemmas while various factors such as business challenges, managerial capabilities, trustworthiness, loyalty, flexibility etc. are related to succession attributes. The findings generally indicate that the respondents agree to adopt succession planning in their businesses even though only half of them have succession planning. A positive relationship among succession planning, successor attributes and succession dilemma is derived based on a correlation analysis. The succession planning model is established with successor attributes and succession dilemma as the determinants for succession planning.